THE INFLUENCE OF SERVICE QUALITY TOWARDS CUSTOMER SATISFACTION to CREATE WORD OF MOUTH (Study on Inpatient of Prima Husada Hospital, Malang) - Kusuma, Kurrotul Desfirea Widya (Jurnal Ilmiah Mahasiswa FEB, 2014)
Service quality is closely related with customer satisfaction because the quality encourages the customer to braid the strong relationship with the company, which is aimed to understand the customer needs and wants. In addition, the demands of health community are increased that make service quality to be one of the important functions that necessary to improve the patient satisfaction. The purpose of this research is to understand and analyze the influence of reliability, empathy, tangibles, assurance, and responsiveness towards customer (inpatient) satisfaction and word of mouth in Prima Husada Hospital. The location of this research is Prima Husada Hospital, Singosari Malang. This hospital is a new hospital in Malang that was established in 2010 and it includes on the general hospital at D class. It chooses because the researcher wants to examine the service quality that is different from large hospital in Malang city and there are small number researches were conducted in this setting. In addition this research was conducted during March - April 2014. The method that has been used to collect the data during the research is questionnaire which has 70 respondents of inpatient in Prima Husada hospital. The duration of data collection is one month which is for age samples are about 10-65 years old. In addition, the data calculation is processed by Structural Equation Model-PLS and SPSS for validity and reliability test. This research shows there is significant influence of assurance and tangible towards satisfaction. Whereas Reliability, Empathy and Responsiveness did not influence significantly towards satisfaction which is proved by the value of t-Statistic of these variables is smaller than t-Table (1,96). On the other hands, the research shows there is significant influence of satisfaction towards WOM. Â  Keywords: Service Quality, Patient Hospitalization, Customer Satisfaction, Word of Mouth